Studies of human leprosy lesions in situ using suction-induced blisters: cell changes with IgM antibody to PGL-1 and interleukin-2 receptor in clinical subgroups of erythema nodosum leprosum - Bhoopat L. (2014)
To examine the immunopathogenesis of type 2 erythema nodosum leprosum (ENL) reactions in leprosy, we studied cellular and soluble immunologic components of skin lesions in 57 patients with reactions (19 acute ENL and 38 chronic ENL), 61 active patients without reactions, and 33 control patients whose leprosy had been treated and cured. Cells, IgM antibody to PGL-1 and Tac peptide levels were obtained from fluid aspirated from blisters induced by suction directly over representative skin lesions. During ENL reactions: a) the lesions in chronic ENL showed a decreased number of CD8+ (T-suppressor) cells and increased helper/suppressor ratio as compared to those in acute ENL and non-reactional leprosy; b) Tac peptide and IgM antibody to PGL-1 levels were elevated in the chronic ENL lesions; c) and systemic administration of corticosteroids appeared to cause a reduction in the intralesional CD4+ cell population and IgM antibody to PGL-1 but did not change CD8+ cell population and the levels of Tac peptide in the lesions. The elevated levels of Tac peptide were localized in the skin lesions while increased levels of IgM anti-PGL-1 seemed to be filtered from the peripheral blood. We conclude that spontaneous lymphocyte activation in situ, primarily of decreased CD8+ and relatively increased CD4+ cells, are important features of chronic, recurrent ENL reactions and may be an intermittent or cyclic phenomenon during the reaction. Understanding the mechanisms of these spontaneous changes in immunity in leprosy will enlarge our knowledge of reactions and of the underlying determinants of delayed type hypersensitivity and cell-mediated immunity in leprosy, which in turn will allow us to realize the potential for artificially manipulating these responses as proposed with vaccines or immunotherapy.